Arabic romantic historical novel (for example works of Abu Hadid) (Journal of Oriental Studies, 2016)
The article discusses the development of the Arab Romantic historical novel example of creativity on the founder of the patriotic novel, the famous Egyptian writer Muhammad Farid Abu Hadid. The novel "The Sorrows of Joh" is dedicated to the popular hero of Arab folklore - Joha. Events unfolding during the conquest of the Arab Caliphate Timur - Central Asian warlord and emir. By its focus this work more inclined to romanticism, which is established in the Egyptian prose and poetry by the end of the second decade of the XX century. In the work of Abu Hadid showed significantly influenced western folklore and literature.
Keywords: romantic historical novel; the hero of Russian folklore; enlightenment; social and human problems